The disruptive effects of COPD exacerbation-associated factors on epithelial repair responses - Kortekaas, Rosa K.; Geillinger-Kästle, Kerstin E.; Fuentes-Mateos, Rocío; van Orsoy, Roël; Al-Alyan, Nakaa; Burgess, Janette K.; Gosens, Reinoud (Frontiers in Immunology, 2024)
Exacerbations of chronic obstructive pulmonary disease (COPD) increase mortality risk and can lead to accelerated loss of lung function. The increased inflammatory response during exacerbations contributes to worsening of airflow limitation, but whether it also impacts epithelial repair is unclear. Therefore, we studied the effect of the soluble factor micro-environment during COPD exacerbations on epithelial repair using an exacerbation cocktail (EC), composed of four factors that are increased in COPD lungs during exacerbations (IL-1β, IL-6, IL-8, TNF-α).Mouse organoids (primary CD31-CD45-Epcam+ cells co-cultured with CCL206 fibroblasts) were used to study epithelial progenitor behavior. Mature epithelial cell responses were evaluated using mouse precision cut lung slices (PCLS). The expression of epithelial supportive factors was assessed in CCL206 fibroblasts and primary human lung fibroblasts.EC exposure increased the number and size of organoids formed, and upregulated Lamp3, Muc5ac and Muc5b expression in day 14 organoids. In PCLS, EC imparted no effect on epithelial marker expression. Pre-treatment of CCL206 fibroblasts with EC was sufficient to increase organoid formation. Additionally, the expression of Il33, Tgfa and Areg was increased in CCL206 fibroblasts from EC treated organoids, but these factors individually did not affect organoid formation or size. However, TGF-α downregulated Foxj1 expression and upregulated Aqp5 expression in day 14 organoids.In conclusion, EC exposure stimulates organoid formation and growth, but it alters epithelial differentiation. EC changes the epithelial progenitor support function of fibroblasts which contributes to observed effects on epithelial progenitors.